1993
DOI: 10.1111/j.1365-2125.1993.tb05892.x
|View full text |Cite
|
Sign up to set email alerts
|

The passage of cloxacillin into cerebrospinal fluid in the absence of meningitis.

Abstract: 1 Eleven patients undergoing lumbar discectomy received cloxacillin by continuous i.v. infusion, starting before the operation. During the operation several blood samples and one CSF sample were taken.2 Mean rate constants describing the passive transfer of drug from plasma to CSF (kp) and the largely active transfer in the opposite direction (kcsF) were estimated. 3 In some subjects the CSF albumin quotient, defined as the ratio between the albumin concentration in CSF and in plasma times 1000, was slightl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…A CRP measurement was not available at the first visit; (2) our patient was much older than previously described successfully treated patients; (3) Immune-mediated transverse myelitis is possible, although there was no response to high-dose IV methylprednisolone; and (4) Cloxacillin has poor lipid solubility and CSF penetration may be insufficient. 17 Furthermore, poor penetration of cloxacillin into abscesses of the central nervous system has been previously described. 18 Failure of IV crystalline penicillin was also noted in a previous report of MSSA myelitis, 12 supporting the hypothesis that penicillins may be a poor choice as monotherapy for bacterial myelitis.…”
Section: Staphylococcus Aureus Myelitis S Karakonstantis Et Almentioning
confidence: 99%
“…A CRP measurement was not available at the first visit; (2) our patient was much older than previously described successfully treated patients; (3) Immune-mediated transverse myelitis is possible, although there was no response to high-dose IV methylprednisolone; and (4) Cloxacillin has poor lipid solubility and CSF penetration may be insufficient. 17 Furthermore, poor penetration of cloxacillin into abscesses of the central nervous system has been previously described. 18 Failure of IV crystalline penicillin was also noted in a previous report of MSSA myelitis, 12 supporting the hypothesis that penicillins may be a poor choice as monotherapy for bacterial myelitis.…”
Section: Staphylococcus Aureus Myelitis S Karakonstantis Et Almentioning
confidence: 99%
“…Le Turnier et al reported lower median (IQR) CSF:plasma ratios and steady state CSF concentrations of 1.8% (1.7%–2.8%) and 0.66 (0.5–0.9) mg/L, respectively, with cloxacillin 12 g IV daily compared with cefazolin [ 7 ]. A 3% ratio of CSF:unbound plasma concentration for cloxacillin has been estimated by others [ 26 ]. Flucloxacillin 2000 mg IV every 4 hours resulted in CSF concentrations of 0.3 mg/L, and others report very low CSF concentrations even when utilizing continuous infusions [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Penetrates in CSF of inflamed meninges to a limited extent, therefore higher doses may be necessary to attain therapeutic targets [106]. Furthermore, therapy failure has been described in patients under treatment for Staphylococcus meningitis [107].…”
Section: Cloxacillinmentioning
confidence: 99%
“…Penetrates in CSF of inflamed meninges to a limited extent, therefore higher doses may be necessary to attain therapeutic targets [106].…”
Section: Flucloxacillinmentioning
confidence: 99%